Determining the equation of surface of additional blade of a screw conveyor - Chasov, Dmitry (Eastern-European Journal of Enterprise Technologies, 2016)
Analysis of directions of upgrading screw conveyors, used for the transportation of chips and sludge, was performed. We conducted analysis of equations of determining critical rotation frequency of the screw, the values of which influences the angle of beginning of movement of material along the blade. Equations of the surface area of additional blade in a general form were analyzed. Using frontal dissection of the gutter, Authors analyzed equation of normal loop taking into account the angle of beginning of movement of material, affected by the angle of attack of the blade. The aim of the work is to obtain equation of the line of intersection of the screw surface and the surface area of additional blades, which possesses considerable value for carrying out calculations and designing constructive parameters of screw conveyors with improved performance for the transportation of metal chips. The formula for determining improved angle of beginning of movement of material along the surface of additional blade was obtained, which allows taking into account the impact of fluid angle. The dependency of equation of the blade surface in the polar coordinate system was described, which gave us the opportunity to develop equation of the line of intersection of the screw surface and the area surface in the parametric form. Authors theoretically substantiated positive impact of additional blades of screw conveyor on decreasing the lifting and driving force for moving the metal chips through the reduction of forces of internal friction of transported metal chips, which is achieved by partial removal by additional blades of the layer of chips from the general stream in the gutter of a screw conveyor. Mathematical dependency for determining effective angle of beginning of metal chips motion along additional blade of the screw’s spiral was obtained, and the law of its movement along the blade was established. We designed, manufactured and tested under laboratory and industrial conditions the prototype sample of a screw conveyor with different angles of attack of additional blades, which can be used in the process of designing similar conveyors for specific workshop conditions.